In-service training as a correlate of teachers' productivity in Nigeria - Sasere, Oluwasola Babatunde (Educenter : Jurnal Ilmiah Pendidikan, 2024)
Teachers are the final mediators of the school curriculum, and their competence level largely impacts students' learning outcomes. This quantitative study aimed to explore the mediation of teacher productivity with the instrumentation of in-service training (INSET) while adopting Social Learning Theory (SLT) as the theoretical framework. A descriptive survey research design was adopted while a multi-stage sampling procedure was used to select samples from a population of 7538 public secondary school teachers and 203 principals in secondary schools in Ekiti state, Nigeria. The sample for this study consisted of 396 participants which comprised of 360 teachers and 36 school principals. Data were gathered and analysed through In-service Training Experience and Impact Questionnaire (ITEIQ) and Teachers' Productivity Questionnaire (TPQ) and Pearson Product Moment Correlation respectively. The study revealed that INSET moderately enhances teacher productivity. The study recommends providing continuous and regular in-service training to teachers in Nigeria to improve their productivity. In addition, such training programs could be designed based on the principles of Social Learning Theory through the instrumentation of collaborative learning, peer mentoring, and feedback mechanisms.